Intact coronary and myocardial functions after 24 hours of non-ischemic heart preservation. (2nd January 2020) - Qin, Guangqi; Wohlfart, Björn; Zuo, Long; Hu, Jingfeng; Sjöberg, Trygve; Steen, Stig
Abstract: Objectives. The aim of this study was to investigate endothelium dependent relaxation (EDR) in coronary artery and the myocardial contractility after 24 h of non-ischemic heart preservation (NIHP). Design. Explanted cardioplegic hearts from six pigs were preserved by NIHP for 24 h. The perfusion medium consisted of an albumin containing hyperoncotic cardioplegic nutrition-hormone solution with erythrocytes to a hematocrit of 10%. Coronary artery ring segments were then studied in organ baths. Thromboxane A2 was used for vasocontraction and Substance P to elicit endothelium dependent relaxation. A heart trabecula from the right ventricle was mounted in an organ bath and a special stimulation protocol was used to characterize myocardial contractility. Fresh cardioplegic hearts from 11 pigs were used as controls. The water content of the hearts was calculated. Results. There was no significant difference between NIHP and fresh controls regarding EDR (91.2 ± 1.2% vs 93.1 ± 1.8%). The contraction force, potentiation and calcium recirculation fraction did not differ between the groups. The water content of the myocardium was 79.3 ± 0.2% for NIHP and 79.5 ± 0.2% for controls. Conclusions. NIHP for 24 h keeps coronary artery EDR and myocardial contractility intact and causes no edema.